Synthesis and antiproliferative activity of 2-arylidene 6-(2-aryl-2-oxoethoxy) benzofuran-3-one derivatives - Demirayak, Şeref; Yurttaş, Leyla; Karaburun, Ahmet Cağrı; Gündoğdu Karaburun, Nalan; Kayagil, İsmail (Bentham Science Publ Ltd, 2016)
The synthesis of 2-arylidene 6-(2-aryl-2-oxoethoxy) benzofuran-3-one derivatives was reported and selected compounds were determined for their anticancer activity evaluation in National Cancer Institute NCI, USA according to the drug screening protocol of the institute against approximately 60 tumor cell lines derived from nine cancer diseases. Compound 3r, namely 2-(4-chlorobenzylidene)- 6-[2-(4-methoxyphenyl)-2-oxoethoxy] benzofuran-3-one exhibited the highest antitumor activity against non-small lung cancer cell lines.
WOS: 000389460600011
Keywords: Antitumor Activity; Aurone; Benzofuranone; Chalcone; Cytotoxic Activity